Intention to visit Malaysian Youth Traveler (Case Study: Ciletuh Palabuhanratu UNESCO Global Geopark) (The Indonesian Journal of Business Administration, 2021)
UNESCO Palabuhanratu global geopark or it can be abbreviated as CPUGG. It is aninternational standard geological, biological, and cultural tourist location located in the Sukabumi areaof West Java. With the name UNESCO as the name of the organization that oversees the existence ofCiletuh Palabuhanratu, it is hoped that this can attract International Travelers to come to CPUGGwhich will have an economic impact on the surrounding area. CPUGG has a problem with the verysmall portion of foreign tourists. So there is a need for research on their intentions to visit touristattractions. In this study, quantitative research was used to determine the regression relationshipbetween motivation and intention to visit tourist attractions.Keywords: Intention to visit, Malaysian Youth traveler motivation, CPUGG